Changes in Area, Yield Gains, and Yield Stability of Sorghum in Major Sorghum‐Producing Countries, 1970 to 2009. Issue 4 (1st July 2014) - Rakshit, Sujay; Hariprasanna, K.; Gomashe, Sunil; Ganapathy, K. N.; Das, I. K.; Ramana, O. V.; Dhandapani, A.; Patil, J. V.
ABSTRACT: Sorghum [ Sorghum bicolor (L.) Moench] is a drought‐resilient crop, grown extensively in semiarid tropics of the world. To understand the scenario of sorghum cultivation across the world, trends in area and yield gain and associated changes in yield stability were analyzed in the top 10 sorghum‐producing countries from 1970 to 2009. Asian countries and the United States recorded a large drop in harvested area. Grain yield levels increased substantially in all the countries except Sudan. Relative to yield level of 1970, sorghum productivity increased annually at 0.96% yr −1 across the top 10 countries analyzed. China (100.9 kg ha −1 yr −1 ) and Nigeria (48.6 kg ha −1 yr −1 ) experienced phenomenal yield gain before reaching a plateau. Overall yield gain was not associated with increased yield stability in a majority of countries except Ethiopia. In fact, in China and India (post‐rainy‐season sorghum), the yield variability increased over time. Genetic gain for grain yield over years in the Indian sorghum improvement program was prominent in rainy‐season hybrid trials (18.5 kg ha −1 yr −1 ), whereas both in post‐rainy‐season hybrid and varietal trials it was insignificant. Much progress in rainy‐season variety trials after 1985 was not observed. Across years in India, the gap between potential and farm yield declined 0.32% yr −1 among rainy‐season cultivars and 0.46% yr −1 among post‐rainy‐season cultivars. The analysis reveals that though substantial progress has been made towards yield gain, this was not represented by increased production because of extensive loss of the sorghum area to other remunerative crops.